Effectiveness of Robotics in Stroke Rehabilitation to Accelerate Upper Extremity Function: Systematic Review - Cora Carrillo; Devyn Tilley; Kaitlyn Horn; Michelle Gonzalez; Cassidy Coffman; Claudia Hilton; Karthik Mani (Occupational Therapy International)
Objective. To examine the effectiveness of robot-assisted therapy (RAT) combined with conventional therapy (CT) compared to CT alone in accelerating upper extremity (UE) recovery poststroke. Data Sources. We searched five databases: Ovid, MEDLINE, CINAHL, PubMed, and Scopus Study Selection. Studies were selected for this review using the following inclusion criteria: randomized controlled trials of adults, RAT combined with CT compared to CT, and Fugl-Meyer Assessment (FMA) as an outcome measure. Studies focused on children with neurological impairments, and studies that used RAT to facilitate lower extremity recovery and/or improve gait were excluded. Data Extraction. The initial search yielded 3,019 citations of articles published between January 2011 and May 2021. Fourteen articles met the inclusion criteria. Randomization, allocation sequence concealment, blinding, and other biases were assessed. Data Synthesis. Current evidence suggests that the use of RAT along with CT may accelerate upper extremity recovery, measured by FMA, in the beginning of rehabilitation. However, the progress fades over time. More empirical research is needed to validate this observation. Also, the findings related to cost-benefit analyses of RAT are inconclusive. Conclusions. It is unclear whether RAT accelerates UE recovery poststroke when used in conjunction with conventional therapy. Given the capital and maintenance costs involved in developing and delivering RAT, more controlled studies examining the effectiveness and cost-benefit analysis of RAT are needed before it can be used widely. This trial is registered with CRD42021270824.